Analisis Komunikasi Interpersonal dalam Mempertahankan Keharmonisan Pernikahan pada Novel Cinta dalam Diam - Nurnajmi Fajriyah; Muhammad Yusuf Siddik; Achmad Yaman; Misroji Misroji (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article analyzes interpersonal communication in maintaining marital harmony as represented in Shineeminka's novel Cinta dalam Diam. The study is based on the view that marriage requires mutual understanding, openness, empathy, and fair conflict management when facing emotional tension, jealousy, misunderstanding, and the presence of a third party. Using qualitative textual analysis, the novel is treated as the primary data source, while books, journal articles, previous studies, Islamic sources, and communication theory are used as secondary data. The findings show that marital harmony in the novel is maintained through five forms of interpersonal communication: opening communication channels, managing power imbalance, recognizing and adjusting to change, respecting individual interests, and resolving conflict fairly. These findings indicate that interpersonal communication is not merely an exchange of messages, but a relational process that builds trust, responsibility, forgiveness, and emotional maturity. The novel also shows that Islamic values such as consultation, patience, justice, and mutual respect strengthen conflict resolution and help restore marital harmony.